Profile of Self-Medication in the Community of Grogol Village Kediri Regency using Traditional Medicine during the Covid-19 Pandemic - Hakim, Abdul; Sugihantoro, Hajar; Syahrir, Ach; Khatijah, Berliana Nur (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
The COVID-19 (Coronavirus disease 2019) Pandemic, caused by the spread of SARS-CoV-2 since 11 March 2020, has compelled society to make such efforts to maintain their health, one of the efforts by using traditional medicine as self-medication. This is also the behavior the Indonesian government suggests through the circular of Health Ministry Number: HK.02.02/IV.2243.2020 about the direction to utilize traditional medicine due to the COVID-19 pandemic. This research aims to get an overview of the use of traditional medicine for self-medication in the society at Grogol Village, Kediri Region, due to the pandemic. This is descriptive research that the data collection is carried out by a non-random sampling method by purposive sampling technique. 100 samples fulfill the inclusion criteria. They are the society that lives at Grogol Village who wills fill out the questionnaire and be interviewed. They have done using traditional medicine for self-medication during the time of the COVID-19 pandemic. The result of the research determines that the purpose of using self-medication is to look after the immune system to stay healthy (48%), the use of self-medication is because it saves cost (27.78%), and the use of traditional medicine is being chosen because of its natural (31.03%). Most of the respondents do not combine traditional medicine and modern one (87%), some respondents do not feel any side effects (72%), and the symptoms that are mostly treated by traditional medicine are catching a cold (36.84).